Implementation pathways of large-scale urban development projects (lsUDPs) in Western Europe: a qualitative comparative analysis (QCA). Issue 6 (2nd June 2020) - Pagliarin, Sofia; Hersperger, Anna M.; Rihoux, Benoît
ABSTRACT: As powerful landmarks to steer local and regional development, strategic projects are often linked with strategic spatial plans. However, the key question remains as to what extent strategic urban projects and plans can be regarded as aligned. By building on previous international comparative research, we identify five main conditions assumed to enable, in combination, the alignment between strategic projects and plans. By adopting a qualitative, multi-method empirical strategy (interviews, site visits, online questionnaire, additional literature) and by performing fuzzy-set Qualitative Comparative Analysis (fs-QCA), we compare 38 European large-scale urban development projects (lsUDPs) and assess which combinations of conditions support concordance of the projects with strategic spatial plans (SSPs). Our analysis shows that there are five pathways, factored out into two main patterns, enabling alignment. Substantial variation in our cases appears to be captured by: (i) considerable involvement of the national state combined with (inter)national private actors and (ii) a considerable involvement of private actors combined with international external events.